Recombination detected in the Heat Shock Protein 90 (HSP90) of the Bemisia tabaci species complex - Kinene, Tonny; Rossito De Marchi, Bruno; Alicai, Titus; Luboobi, Livingstone S.; Abu Omongo, Christopher; Savill, Anders; Boykin, Laura M. (bioRxiv, 2019)
Bemisia tabaci (whiteflies) are a global insect pest causing billions of dollars in damage each year, leaving farmers with low yields. In East Africa, whiteflies are superabundant and present on cassava plants throughout the year. Whiteflies do not decrease in number in the hot dry seasons in East Africa, therefore, it has been suggested that the synthesis of Heat Shock Protein (HSP) may protect the whitefly from heat stress and other biotic factors. In this study we used data sequence generated from individual whiteflies to assess variability and recombination of the HSP90 gene in members of the B. tabaci species complex. Results A total of 21 samples were sequenced on Illumina Hiseq 2500 and Hiseq 4000. These included eight genetic groups of B. tabaci: 7 SSA1, 5 SSA2, 2 Australia I (AUSI), 2 New World Africa (NWAfrica), B. afer, Uganda, Mediterranean (MED), and Middle East Asia Minor 1 (MEAM1). An alignment of 21 HSP90 sequences was generated after mapping and de novo assembly. Recombination analysis was performed on an alignment of 27 HSP90 sequences (we added an additional 6 sequences from GenBank). There were 18 recombination events detected in the HSP90 gene of the B. tabaci species complex, 7 of which were regarded as events that could be caused by evolutionary mechanisms such as gene duplication other than recombination. The phylogenetic analysis carried out on dataset without recombination events revealed a tree pattern with short terminal branches. Conclusion Recombination events were detected for members of the B. tabaci species complex in the HSP90 gene. This could explain the variability in the HSP90 gene of the B. tabaci species complex and highlight the phenomenon of the increased chance of survival and reproductive abundance of whiteflies in hot conditions in East Africa, since recombination is a major driving force of evolution.
Keywords: Recombination; HSP90 gene; Climate change; Bemisia tabaci; Food security